Fiber Nonlinearity Equalizer Based on Support Vector Classification for Coherent Optical OFDM - Tu Nguyen; Sofien Mhatli; Elias Giacoumidis; Ludo Van Compernolle; Marc Wuilpart; Patrice Megret (IEEE Photonics Journal)
A support vector machine (SVM)-based classification nonlinear equalizer (NLE) is demonstrated, for the first time, in coherent optical orthogonal frequency-division multiplexing (CO-OFDM). For a 40-Gb/s 16 quadrature amplitude modulated (16QAM) CO-OFDM system at 400 km of transmission, SVM-NLE reduces the fiber-induced nonlinearity penalty by about 1 dB in comparison to the benchmark artificial-neural-network (ANN)-based and inverse-Volterra-series-transfer-function-based NLEs.